The Stance of Semi-Popular Articles about Language Learning - Riani, Eva; Darya, I Wayan (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2022)
This study aims to analyze how the writers of semi-popular science articles express their stances when writing about language learning discipline. This research used corpus-based analysis approaches with the help of AntConc application to analyze the stance marker in the corpus. The analysis is conducted by adopting Hyland's framework of stance. The data source of this research is 81 articles about language learning from various university and institution web magazines. The result found that in expressing their stance, the writers of semi-popular science articles employ many hedges in form of the modal verb to mark their tentative and carefulness, booster in the form of reporting verb to increase the newsworthiness of the articles, attitude marker in the form of a positive adjective to express their positive attitude toward the study, and self-mention in the form of the singular pronoun when referring to researcher and plural pronoun when referring to the writer themselves.